Current trends in the management of chronic myelogenous leukemia - Hehlmann, Rüdiger; Hochhaus, Andreas; Berger, Ute; Reiter, Andreas (Annals of hematology, 2000)
The management of chronic myelogenous leukemia (CML) has become complex due to the availability of improved diagnostic procedures and life-prolonging or even curative treatment strategies that are more successful the earlier they are applied in the course of the disease. This is true for allogeneic bone-marrow transplantation, treatment with interferon α (IFN) and Philadelphia-negative stem-cell collections for autografting. Outcome differs according to risk profiles of patients at diagnosis. In addition, molecular techniques for the detection of the BCR-ABL fusion gene or its products, such as the reverse-transcriptase polymerase chain reaction (PCR), Southern blot analysis, or fluorescence in situ hybridization, facilitate accurate diagnosis and the monitoring of residual disease. They allow the individualization of treatment such as early infusion of donor lymphocytes if molecular relapse is detected after allografting, or discontinuation of IFN in the presence of very low BCR-ABL transcript levels). The availability of real-time PCR devices further improves and accelerates the diagnosis and monitoring of residual disease. This article addresses recent developments in drug therapy and allografting, including treatment intensification with low-dose ara C or intensive chemotherapy followed by autografting, introduction of new drugs (such as homoharringtonine or tyrosine kinase inhibitor STI571), progress with unrelated donor transplantations, use of peripheral blood stem cells for allografting, and transplantation without myeloablative conditioning. Tradeoffs between the treatment options will be discussed in the context of the evidence-based guidelines for treating CML, as recently published by the American Society of Hematology. Finally, the new competence network on acute and chronic leukemias will be introduced.